Analysis of Mothers' Knowledge About Postpartum Visits in the Work Area of Gunung Tua Community Health Center - Wulandari, Ratna; Suzani, Liana Fitri; Manurung, Ernita (PT Inovasi Pratama Internasional, 2025)
The postpartum period is a fairly important period for health workers to always monitor because less than optimal implementation can cause the mother to experience various problems, and can even lead to postpartum complications. Among the causes of maternal death, infection is the second most common cause of death after bleeding. The type of research used was descriptive, namely, to determine the mother's knowledge about postpartum visits. The sampling technique used in this study was total sampling. The total population is a sampling technique in which the total number of samples is the same as the population (Sugiyono 2010). Thus, the sample in this study was the entire population of postpartum mothers-form January to August 2024 in the Gunung Tua Health Center work area, totaling 34 people. Based on the data analysis conducted, it is known that the majority of respondents' knowledge is in the lowers category, (38.2%). This is understandable, considering that the majority of respondents' education was in the basic education category, (44.1%). Education is a formal and non-formal activity in an effort to develop a person's mindset, personality, and abilities, both inside and outside of school, as well as life experiences that last a lifetime. The majority of the respondents' knowledge was in the sufficient category, (17.6%). This is understandable, considering the majority of respondents' ages in the 21-35 year category, namely (47.0%). Most respondents' knowledge was in the insufficient category, (20.6%). This is understandable, considering that the majority of respondents' jobs were in the unemployed/housewife category, (44.1%). Every health worker, especially midwives, should be able to provide counseling to mothers regarding the importance of visits during the postpartum period.